Cerebellopontine Angle Epidermoid Cysts: Surgical Treatment Outcome - Mohamed I. Refaat; Omar Y. Abdallah (Indian Journal of Neurosurgery)
Background  Epidermoid cysts (ECs)are an uncommon slowly growing congenital lesions. The cerebellopontine angle (CPA) is the most common site. Surgical management for these lesions remains challenging due to the high-adherence of the cyst capsule to the surrounding structures and its tendency to present with invasion of multiple cisterns. Objective The aim of this study was to evaluate the clinical and radiological outcome of surgically treated ECs in the CPA region. Materials and Methods This is a retrospective study conducted on patients presenting with symptomatic CPA ECs. Clinical outcome was assessed in terms of improving or worsening of the presenting symptoms. Radiological outcome was assessed by comparing the tumor size, brainstem, and cerebellar compression in the preoperative and postoperative images. Results In this study, 18 patients were included. All cases were operated upon by microsurgical evacuation of the cyst contents and excision of the nonadherent parts of the capsule. On admission, cranial nerve symptoms predominated. Improvement or resolution of preoperative deficits was seen in 15 patients. Preoperative symptoms worsened in two and new postoperative symptoms occurred in one patient. Seven patients needed additional ventriculoperitoneal (VP) shunt in the same setting due to the presence of hydrocephalus. During the follow-up period, symptomatic recurrence occurred in one patient, while asymptomatic recurrence occurred in one patient. Conclusion Surgical management of CPA ECs, leaving remnants of the capsule on cranial nerves and brain stem can be considered as a relatively safe surgical procedure with a good clinical outcome and low-recurrence risks.